Developing an electronic geriatric assessment to improve care of older adults with cancer receiving radiotherapy - VanderWalde, Noam A. (Tech Innov Patient Support Radiat Oncol, 2020)
Older adults make up a substantial proportion of patients diagnosed with cancer. Gaps in evidence of care for older adults with cancer leads to treatment heterogeneity and poor outcomes. Medical and Surgical Oncology clinics throughout the world are increasingly using Geriatric Assessment (GA) based approaches to treatment that are beginning to improve care through treatment decision-making communication, health-related quality of life outcomes, and reducing chemotherapy toxicities. Yet, GA based approaches are not often used in radiation oncology clinics. This manuscript aims to describe the ongoing development of an electronic patient-reported GA with real-time data interpretation and recommendation delivery to help increase the use of a personalized GA based approach to the care of older adults within radiation oncology clinics. Future studies demonstrating the utility and benefit of GA based approaches to help older adults undergoing radiotherapy for their cancers are still sorely needed.